Tendência de longo prazo das finanças públicas no Brasil - José Carlos Jacob de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– This paper analyses the behavior of Brazilian public finances, for the period between 2000 and 2015. Therefore a simulation is made using a simple model built in order to predict Brazilian public deficit, above and below the line, and which uses, on a base line, a supposed economic stability, with an annual GDP average growth rate of 4%. In that simulation it is supposed that Brazilian central government will lose important revenues and, at the same time, it is supposed that the other current and capital expenditures will increase in real terms along the analysed period. Besides that, it has been shown that it will be possible to stabilize the public debt/GDP ratio, between 2001 and 2015, at a 51,5% rate, which stands above the 46,5% goal that the government had established during the issuance of the so called Fiscal Stabilization Program. Several other simulations have been provided in order to show the great sensitivity of the debt/GDP ratio to economic growth rate as well as to interest rates. Meanwhile, it has been possible to show that even using the 4% growth rate hypothesis, it's not very difficult for the government to make the debt/GDP ratio fall to a rate of 40%, by the end of 2015, if the CPMF contribution (or a similar tax) is antained, although at a smaller rate, and also if a substitute for the so called "conta-petróleo" is approved or, if the other current and capital expenditures rate of real growth is alternatively reduced, along the period.
Keywords: 330